The Role of Management Principles in Improving the Effectiveness of Arabic Language Learning Programs in Madrasah Tsanawiyah Pekanbaru City - Winta Fevi Camelia; Hakmi Wahyudi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze the role of management principles in improving the effectiveness of Arabic language learning programs in Madrasah Tsanawiyah in Pekanbaru City, Indonesia, with a focus on the principles of reciprocity and centralization. Previous studies have rarely integrated reward systems and centralized curriculum policies in Arabic language learning management. This study employed a descriptive qualitative approach involving two Arabic language teachers and one madrasah principal from MTs Masmur and MTs Al-Fajar. Data were collected through observation, in-depth interviews, and documentation. The findings show that the application of management principles planning, organizing, implementation, and evaluation contributes to improving learning effectiveness. The principle of reciprocity enhances teacher motivation through financial and non-financial rewards, which encourage more innovative teaching practices. Meanwhile, the principle of centralization helps maintain curriculum consistency but may limit teachers' flexibility in adapting learning to students’ needs. The hybrid management model, defined as the integration of centralized curriculum standards with limited teacher autonomy in instructional practices, has proven to support adaptive and effective Arabic language learning. This study emphasizes the importance of balancing reward systems and centralized policies to improve teacher performance and the effectiveness of Arabic language learning in the madrasah environment.